Sensor Measurements Can Characterize Fluctuations and Wearing Off in Parkinson’s Disease and Guide Therapy to Improve Motor, Non-motor and Quality of Life Scores - Farzanehfar, Parisa; Woodrow, Holly; Horne, Malcolm (Frontiers in Aging Neuroscience, 2022)
Objectives. The aim was to examine the role of sensor measurement in identifying and managing fluctuations in bradykinesia of Parkinsons Disease. Method. Clinical scales and data from wearable sensors obtained before and after optimisation of treatment from 107 participants who participated in a previous study was used. Fluctuators were identified by a levodopa response or wearing off in their sensor data and were subdivided according to whether the sensor’s bradykinesia scores were in target range, representing acceptable bradykinesia for part of the dose (Controlled Fluctuator: n=22) or above target for the whole dose period (Uncontrolled Fluctuator; n=28). Uncontrolled Non-Fluctuators (n=24) were cases without a levodopa response or wearing-off and Sensor bradykinesia scores above target throughout the day (un-controlled). Controlled Non-Fluctuators (n=33) were below target throughout the day (controlled) and used as a reference for good control (MDS-UPDRS III = 338.6 and PDQ39 =2818). Results. Treating Fluctuators significantly improved motor and quality of life scores. Converting fluctuators into Controlled Non-Fluctuators significantly improved motor, non-motor and quality of life scores and a similar but less significant improvement was obtained by conversion to a Controlled Fluctuator. There was a significantly greater likely hood of achieving these changes when objective measurement was used to guide management. Conclusions. The sensor’s classification of fluctuators bore a relation to severity of clinical scores and treatment of fluctuation improved clinical scores. The sensor measurement aided in recognising and removing fluctuations with treatment and resulted in better clinical scores, presumably by assisting therapeutic decisions.